Comparative study of antioxidant level and activity from leaf extracts of Annona muricata Linn obtained from different locations - Syed Najmuddin, Syed Umar Faruq; Mohammed Alitheen, Noorjahan Banu; Hamid, Muhajir; Nik Abd Rahman, Nik Mohd Afizan (Universiti Putra Malaysia Press, 2017)
Annona muricata Linn possesses an anti-tumorigenic effect towards cancer. Several of its bioactive components have already been assessed in previous findings. However, none of the previous studies actually addressed the important consideration of the association between cultivation area of this medicinal plant and its bioactive compounds/antioxidants. In this study, the antioxidant level and antioxidant activity of 19 Annona muricata collected from different locations were evaluated by phenolic and flavonoid assays together with Oxygen Radical Absorbance Capacity (ORAC), Ferric Reducing Ability of Plasma (FRAP) and 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) assays. M1 was found to have an attractive antioxidant profile as it had the highest content of phenolics (73.2 µg/mL GAE) and flavonoids (191.4 µg/mL CE) and also the highest antioxidant capacity in ORAC assay (254.7 µM). Additionally, it had a favourably high ferric ion reducing capacity (15.55 µM Fe2+/µg) and the best free DPPH-radical scavenging activity (IC50=143.5 µg/mL). On the contrary, R1 showed the lowest level of phenolics with a GAE value of 21.92 µg/mL, ranked second lowest in flavonoid content (65.42 µg/mL CE), and it had the least antioxidant capacity in ORAC (94.66 µM), FRAP (4.17 µM Fe2+/µg) and DPPH assays (1597 µg/mL), making it the least desirable antioxidant source. Based on this finding, it was concluded that Annona muricata Linn had varied antioxidant levels and activity regarding its cultivation area; hence, it would be a guide in the selection of potential candidates for natural antioxidants in phytopharmacy.